The world is flat a brief history of the twenty-first century - Friedman, Thomas L. (Farrar, Strauss and Giroux, 2006)
The World Is Flat is Thomas L. Friedman's account of the great changes taking place in our time, as lightning-swift advances in technology and communications put people all over the globe in touch as never before--creating an explosion of wealth in India and China, and challenging the rest of us to run even faster just to stay in place. Friedman offers a concise history of globalization, discussing a wide range of topics, from the September 11 terrorist attacks to the growth of the middle class in both China and India.This updated and expanded edition features more than a hundred pages of fresh reporting and commentary, drawn from Friedman's travels around the world and across the American heartland--from anyplace where the flattening of the world is being felt.